The impact of teacher well-being and mental health on pupil progress in primary schools. Issue 4 (3rd September 2019) - Glazzard, Jonathan; Rose, Anthea
Abstract : Purpose: The study was based around the following three research questions: What factors affect teacher well-being and mental health? How does teacher well-being and mental health impact on the progress of students? What resilience strategies are used by highly effective teachers with poor mental health to ensure that their students thrive? The paper aims to discuss this issue. Design/methodology/approach: The research study was qualitative in nature and involved ten primary schools in England. Teachers and head teachers were interviewed. Each school visit also included a pupil discussion group with children from Years 3. In total, the research team interviewed 35 education professionals and 64 pupils. Findings: Teachers reported a number of work-related stress triggers including busy times of the year, such as assessment periods, the pressure of extra curricula activities, the unexpected, keeping up with the pace of change and changes in school leadership. Children were attuned to their teacher's mood and could usually pick up when they were feeling stressed, even if teachers tried to hide it. Originality/value: No studies have used pupil voice to explore pupil perspectives of the impact of teacher mental health on their learning and progress. This is the first study of its kind.